MICROBIAL FUEL CELL (MFC) MENGGUNAKAN BAKTERI BACILLUS SUBTILIS DENGAN SUBSTRAT LIMBAH SEPTIC TANK SERTA PENGARUHNYA TERHADAP KUALITAS LIMBAH - Fitra Adi Prayogo; Agung Suprihadi; Budi Raharjo (Jurnal Akademika Biologi, 2017)
The power plant was still dependent on non-renewable energy is one factor in Indonesia fixed with the problems of electric energy crisis. Several lecturer have shown that B. subtilis can produced electricity through Microbial Fuel Cell (MFC). The purpose of this study is to measured the values of voltage, electric current, and power density as well as changes in the quality of waste water septic tank. Waste in a vacuum toilet can be of service "Doremon Jaya", sterilized and counted the value of the quality of wastes. B. subtilis inoculum was then inoculated into a bioreactor containing sterile waste septic tank with 4 different concentrations of 0%, 1%, 2% and 3% (v/v). Inoculum was incubated for 12 hours prior to observing. The result showed that B. subtilis with inoculum concentration of 3% (v/v) produced the greatest voltage, which is 299.70 mV on 4-hour with strong current and power density 0.2997 mA 8.98 mW / cm2. COD can reduced by up to 31.18% at the inoculum concentrations of 3% (v/v), while the value of BOD reduced by up to 25.03% at the inoculum concentrations of 3% (v/v). DO value also experienced the percentage decreased to 34.25% or decreased to 0.96 at the inoculum concentrations of 2% (v/v). pH value in the treatment of inoculum concentrations of 0%, 1%, 2% and 3% (v / v) decreased after the fermentation was consecutively 5.4, 4.8, 4.9, and 4.2  Kata kunci : Bacillus subtilis, Microbial Fuel Cell, Septic  tank, Wastewater quality